(untitled) (Global Journal of Human-Social Science, 2013)
This paper provides core understanding about phenomenon of migration to big cities from coastal villages of Bangladesh. It describes major push-pull factors, how migration contributes to reduce or increase vulnerabilities and impacts of migration. The paper also depicts lives and livelihoods scenario of five study villages. Livelihood sources of coastal communities particularly agriculture and fisheries are climate sensitive. This micro level study examines how coastal people perceive climate change on their various activities, cross-seeking it with scientific shape, and their responses to climate change. Findings reveal that many migrants are enforced to move in response to changes in conditions (or in their perception of conditions) at the places of origin.